MENINGKATKAN HASIL BELAJAR DENGAN MODEL PROBLEM BASED LEARNING PENDEKATAN CULTURALLY RESPONSIVE TEACHING DI SMP - Lissya Pramaishella Putri; Yessi Fitriani (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research is Classroom Action Research which aims to improve student learning outcomes in class VII.3 at SMP Negeri 10 Palembang by applying the Problem Based Learning (PBL) learning model with a Culturally Responsive Teaching (CRT) approach. The research subjects were 34 students in class VII.3 at SMP Negeri 10 Palembang. This research was conducted because student learning outcomes were low. Data collection techniques are observation and tests. This research was carried out in 2 cycles. In cycle I, only 17 students completed their studies with a percentage of 50%. In cycle II, 29 students had completed their studies with a percentage of 85%, while 5 other students had not yet completed their studies with a percentage of 14.7%. Thus it can be concluded that the application of the Problem Based Learning (PBL) learning model with a culture-based approach (CRT) can improve student learning outcomes.